Bakteri Asam Laktat dari Peda, Bekasam, Terasi dan Rusip Penghambat Morganella Morganii (Pembentuk Histamin) - Rinto, Rinto (Jurnal Penelitian Pertanian Terapan, 2011)
The aim of this research is find out the lactic acid bacteria (LAB) from peda, bekasam, terasi and rusip which had antagonis by Morganella morganii (histamin producer bacteria). The result was that the number isolate from peda was 3 (1P1 104, 3P1 104, 2P2 104), bekasam was 7 (1B1 104, 2B1104, 1B2104, 2B2104, 3B2 104, 1B1 105, 2B1105), terasi was 4 (1T1 104, 2T1 104, 3T1 104) and rusip was 5 isolates (1R1103, 2R1103, 3R1103, 1R1104, 1R2104). All the isolates was bacill, gram positive, and negative catalase. The isolate which had biggest of clear zone was 3B1104 and 1T11104, with the diameter of clear zone was 1.725 cm and 1.300 cm. Keywords: Antagonis, Lactic acid bacteria, Morganella morganii